Isokinetic strength and experience: Analyzing key attributes in professional soccer players - Hacı Ahmet Taşpınar; Alparslan İnce; Necdet Apaydın; Cengiz Ölmez (Turkish Journal of Kinesiology)
Soccer is one of the sports where performance is shaped by the coming together of numerous variables. The importance of strength, a physical variable that determines performance, is thought to be as crucial as the experience levels of athletes, which are also considered important for performance. The present study aimed to compare the isokinetic strength characteristics and soccer experience of professional league (PRL) and amateur league (AML) soccer players. After recording variables such as total playing seasons and weekly training sessions, isokinetic strength measurements were conducted at angular velocities of 60°/sec and 180°/sec. The outcomes revealed that PRL players engaged in significantly more weekly training sessions and had accumulated a higher total number of playing seasons than their AML counterparts (p